Release and Demand of Public Health Information in Social Media During the Outbreak of COVID-19 in China - Tang, Songjia; Wu, Xiaoxin; Chen, Jingjing; Lu, Fangfang; Zhang, Zhihao; Xu, Yingying; Zhang, Jufang (Frontiers in Public Health, 2022)
Information release is a key to the macro-economy during the outbreak of the COVID-19. To explore the relationship between information supply by the government and public information demand in the pandemic, this study collected over 4,000 posts published on the most popular social media platform, i.e., WeChat. Many approaches including text mining are employed to explore the information at different stages during the pandemic. According to the results, the government attached great importance to the information related to the pandemic. The main topics of information released by the government included the latest situation of the pandemic, announcements by the State Council, and prevention policies for COVID-19. Information mismatch between the public and Chinese governments contributed to the economic depression caused by the pandemic. Specifically, the topics of “the latest situation” and “popular scientific knowledge regarding the pandemic” gained the most attention of the public. The information demand of the public changed from the pandemic itself to the recovery of social life and industrial activities after the authority announced the control of pandemic. However, during the recession phase, the information demand shifted to asymptomatic infections and global pandemic trends. By contrast, some of the main topics provided by the government such as “How beautiful you are” were excessive because the public demand is insufficient. Therefore, severe mismatches existed between information release of the government and public information demand during the pandemic, which impeded the recovery of the economy. The results in this study provide strategical suggestions of information release and opinion guidance for the authorities.